Para mejorar el desempeño académico desde el área de ciencias sociales (2019)
Critical thought is one of the ways of thinking about any topic, content or issue. With critical thought, people improve the quality of their own thoughts by grabbing everything considered inherent in the act of thinking and, hence, strengthens their intellectual development. Therefore, we understand that critical thought allows us to analyse and evaluate the consistency of reasoning, developing certain skills considered as fundamental, such as the ability to interpret thoughts, situations, and information of multiple kinds, not only in the classroom, but also in daily life. This investigation was carried out with the objective of setting up a proposal in order to develop critical thought on students of 7th grade from the I.E. Jesus Maestro of Soledad from the social sciences area to improve their performance academically; in this way, they will be able to overcome the low grades they have been showing academically and scholar repetition detected in the late years. This investigation can be classified as positivist, attending to empiricism, from a quantitative approach, descriptive and transectional; with a finite population, represented by the students, teachers and parents from 7th grade. In order to obtain the information needed, we used a technique based in surveys with questionnaires as instrument. The results allowed us to design pedagogical guidelines for strategies to develop the critical thought from the social sciences area in the 7th-grade students of the institution.